The Microcontroller Stand for Investigation of Tripping Thresholds of Voltage Control Relays for Household Consumers - Zorin, Yevhenii; Chepeliuk, Oleksandr (2022 IEEE 3rd KhPI Week on Advanced Technology (KhPIWeek), 2022)
In the study of voltage control relays the problem of voltage adjustment accuracy is occurred. During execution of experiments with voltage control relays the preset increasing or decreasing voltage velocity is mandatory. This paper examines the design features of the laboratory stand for investigation of tripping thresholds of voltage control relays for household consumers. The main focus is applied to the possibility of increasing or decreasing the voltage value with the preset constant velocity precisiously and automatically. Furthermore the servo drive based on stepping motor under control of microcontroller is described in detail which is needed for satisfying all of mentioned requirements. Much attention is payed not only to solutions implemented in electrical circuit of laboratory stand but also to microcontroller programming solutions. The figures with appearance of laboratory stand and electrical circuit diagrams are presented. In conclusion authors show that laboratory stand allows to withdraw the protective tripping characteristic of the voltage control relay at unacceptable voltage deviations with a small error and in lesser time because the influence of human factor during increase or decrease of voltage at required velocity is excluded. This paper might be useful for the specialists in this or similar subject area, for instance investigations of protective voltage relays for industrial applications.